Advancing Culture of Living with Landslides: Volume 1 ISDR-ICL Sendai Partnerships 2015-2025 - Sassa, Kyoji; Mikoš, Matjaž; Yin, Yueping (WLF: Workshop on World Landslide Forum, 2017)
Landslide Science; International Strategy for Disaster Reduction; Landslide Hazard Assessment; Landslide Dynamics; Landslide Risk Reduction